A dual‐patch polarization rotation reflective surface and its application to wideband wide‐beam low‐profile circularly polarized patch antennas. Issue 2 (26th September 2018) - Chen, Qiang; Zhang, Hou; Xiong, Ling‐Heng
Abstract: This study investigates the use of a polarization rotation reflective surface (PRRS) to construct a wideband, wide‐beam, low‐profile circularly polarized (CP) patch antenna. The device is composed of a feeding monopole antenna and a novel PRRS‐based dual‐patch artificial magnetic conductor (AMC) cell structure. The PRRS has two polarization rotation (PR) frequency points, generated by properly adjusting the width between square and L‐shaped metallic patches. A large PR band of 35.5% (5.1‐7.3 GHz) was achieved by combining two adjacent PR frequency points. The PRRS‐based patch antenna impedance bandwidth was measured to be 28.6% (5.1‐6.35 GHz), with a 3 dB axial ratio (AR) bandwidth of 21.8% (4.8‐6.4 GHz) and a profile of 0.045 λ 0 . Additionally, the proposed antenna exhibited the largest AR beamwidth (to our knowledge) of 175° and 128° in the xoz and yoz planes, respectively. It also produced a high broadside gain of 6.7 dBic within the operational bandwidth.